PELATIHAN TERAPI PERMAINAN KOOPERATIF SEBAGAI UPAYA MENGATASI TEMPER TANTRUM PADA ANAK PAUD DAN TK DI KECAMATAN AMBARAWA: Cooperative Game Therapy Training As An Effort To Resolve Temper tantrum In Children In Early Childhood Education Program And Kindergarten District Of Ambarawa - wulansari; Fiktina Vifri Ismiriyam; MUKHAMAD MUSTA'IN (UPPM - STIKES Pemkab Jombang, 2019)
Abstract Temper Tantrum is an uncontrolled emotional outflow in children, which often occurs in preschool children. The lack of understanding of teachers and parents in dealing with children with temper tantrum can result in unfavorable to the child's psychological development. Provision of appropriate information and skills on handling temper tantrums through cooperative game therapy to students, teachers and parents, is considered as an effort to prevent or minimize the appearance of temper tantrums. The purpose of this activity is the high participation of students in cooperative games and increasing the knowledge of teachers and parents of students about handling children with temper tantrums through cooperative games. The method used is screening knowledge about temper tantrums, then the implementation of cooperative game training is 2 meetings. The result of this service activity is that all students participate in cooperative games. Besides the participants' knowledge (teachers and parents), at the time of the pretest knowledge was 40% less, 35% Fair and 25% Good and at the posttest knowledge was 5% Less, 35% Fair and 65% Good. Thus it can be concluded there is an increase in the knowledge of participants to a large extent good. Thus through community service, the participants are expected to be able to carry out prevention of Temper tantrum properly.